2014
DOI: 10.4142/jvs.2014.15.4.519
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing effects of serum-rich and cytokine-supplemented culture conditions on developing blastocysts and deriving porcine parthenogenetic embryonic stem cells

Abstract: The present study was conducted to develop an effective method for establishment of porcine parthenogenetic embryonic stem cells (ppESCs) from parthenogenetically activated oocyte-derived blastocysts. The addition of 10% fetal bovine serum (FBS) to the medium on the 3rd day of oocyte culturing improved the development of blastocysts, attachment of inner cell masses (ICMs) onto feeder cells, and formation of primitive ppESC colonies. ICM attachment was further enhanced by basic fibroblast growth factor, stem ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…To date, a variety of efforts have been conducted to establish ESCs derived from inner cell mass (ICM) of blastocysts in porcine species (Telugu et al, 2011;Jung et al, 2014;Hou et al, 2016), and successful establishment efficiency of porcine ESCs was dependent on age and source of porcine embryos, isolation methods of ICM from blastocysts, components of culture medium, and types of selfrenewal-related cytokines and feeder cell layers (Vackova et al, 2007;Xue et al, 2016). However, although a variety of attempts have been widely conducted, the establishment efficiency of ESCs from porcine blastocysts is still and extremely low.…”
Section: Establishment Of In-vitro Culture System For Enhancing Produmentioning
confidence: 99%
“…To date, a variety of efforts have been conducted to establish ESCs derived from inner cell mass (ICM) of blastocysts in porcine species (Telugu et al, 2011;Jung et al, 2014;Hou et al, 2016), and successful establishment efficiency of porcine ESCs was dependent on age and source of porcine embryos, isolation methods of ICM from blastocysts, components of culture medium, and types of selfrenewal-related cytokines and feeder cell layers (Vackova et al, 2007;Xue et al, 2016). However, although a variety of attempts have been widely conducted, the establishment efficiency of ESCs from porcine blastocysts is still and extremely low.…”
Section: Establishment Of In-vitro Culture System For Enhancing Produmentioning
confidence: 99%
“…They show a large, flat and round (polygonal in rare cases) shape with compact colonies and distinct borders, with relatively small diameters and a high nucleus-to-cytoplasm ratio, a single nucleus with multiple nucleoli, and are sensitive to tryptase. These cells grow more slowly and have limited capability to be integrated into host blastocysts [92,120,122,134,141,143] . Another type of porcine PSCs was shown to have a mouse ESCs morphology, i.e., small, not flat and with a compact, glistening, doom shaped appearance.…”
Section: Criteria For Evaluating Pluripotency In Porcine Stem Cellsmentioning
confidence: 99%
“…The facts that outgrowths and AKP-positive colonies could be isolated and cultured from porcine pre-implantation embryos indicated that there were pluripotent cells in the porcine embryos. However, the culture medium, most of which was modified from mouse ESCs or human ESCs culture medium, could not provide an effective environment for maintaining the self-renewal and proliferation of these putative porcine pluripotent cells, as it does for mouse ESCs and human ESCs establishment[ 23 25 ]. LIF and bFGF are the most important cytokines in the culture medium for maintaining the pluripotency of mouse ESCs [ 26 ] and human ESCs, respectively [ 27 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…LIF and bFGF are the most important cytokines in the culture medium for maintaining the pluripotency of mouse ESCs [ 26 ] and human ESCs, respectively [ 27 30 ]. Although there have been reports showing that there is no LIF receptor in porcine ICM cells [ 31 , 32 ], studies on porcine pluripotent cell lines have shown that the porcine pluripotent signalling pathway might depend on both LIF and bFGF [ 25 , 32 ]. Therefore, the signalling pathway that regulates porcine pluripotency is still an open scientific question.…”
Section: Introductionmentioning
confidence: 99%